Lecturer Learning Development Model Based on E-Learning and Self-Directed Learning to Improve Adaptation to Changes in the Higher Education Curriculum in South Sulawesi - Makkuradde, Andi Syahrul; Asy’ari, Abu Hasan; Pratama, Moch. Givan Andra; Abidin, Zainal; Sudirman, Sudirman (International Journal on Advanced Science, Education, and Religion, 2025)
This study develops and tests lecturer learning models based on e-learning and self-directed learning (SDL) to improve adaptation to curriculum changes in South Sulawesi universities, Indonesia. With a research and development (R&D) approach using the ADDIE framework, the research involved 120 lecturers from various universities. Data were collected through questionnaires, interviews, observations, and expert validation, and analyzed using descriptive statistics, t-tests, ANOVA, and thematic analysis. The developed model consists of four main components: (1) microlearning modules tailored to curriculum reform needs, (2) Digital Pedagogy Toolkit to support innovative teaching practices, (3) Community of Practice (CoP) for peer collaboration, and (4) Monitoring & Analytics Dashboard for data-driven feedback. The validation results showed high feasibility and relevance, while the effectiveness testing showed a significant increase in pedagogical competence, technological readiness, and proactive attitude of lecturers in adapting. Qualitative findings reveal increased motivation, collaborative engagement, and confidence of participants. This model has proven effective in encouraging the independent professional development of lecturers based on technology, with practical implications for integration into college professional development programs. Recommendations include infrastructure support, differential learning pathways, and participation incentives. Follow-up research is recommended to evaluate long-term impacts, adaptations in various contexts, and measurement of student learning outcomes.